2022
DOI: 10.1371/journal.pone.0270186
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice regarding diabetes and hypertension among school students of Nepal: A rural vs. urban study

Abstract: Background The burden of non-communicable diseases like diabetes and hypertension is increasing worldwide including low-and middle-income countries. Good knowledge of such diseases among young people will make them adopt a healthy lifestyle from an early age, which will, in turn, prevent them from developing such non-communicable diseases. This study aimed to assess the knowledge, attitude, and practice of rural and urban school students regarding diabetes and hypertension. We also aimed to see the differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
4
6
0
Order By: Relevance
“…These results joined different published results among non-diabetic adults in different countries including Jordan [14], Ethiopia [4,20], India [21] and Saudi Arabia [22]. However, lower rates were reported in Kenya [23], Pakistan [17], Philippines [24], Bangladesh [25], Qatar [12] and Saudi Arabia [26] while higher rates of knowledge were also reported in other countries citing Sri Lanka [15] and Bangladesh [27]. These variations in the level of knowledge in different countries are to be treated with some care due to the difference in the target population (students, general public…) or in the measurement systems (difference in the used items and cut-off points) [14].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…These results joined different published results among non-diabetic adults in different countries including Jordan [14], Ethiopia [4,20], India [21] and Saudi Arabia [22]. However, lower rates were reported in Kenya [23], Pakistan [17], Philippines [24], Bangladesh [25], Qatar [12] and Saudi Arabia [26] while higher rates of knowledge were also reported in other countries citing Sri Lanka [15] and Bangladesh [27]. These variations in the level of knowledge in different countries are to be treated with some care due to the difference in the target population (students, general public…) or in the measurement systems (difference in the used items and cut-off points) [14].…”
Section: Discussionsupporting
confidence: 85%
“…In this study, some factors including the level of education, sex, marital status, living area, smoking, sports practice and having a family history of diabetes were not associated with the level of knowledge about this disease. Consistent results were obtained for some of these factors [15,24,27]. Contrarily, other studies found that that living area [24,27], family history of diabetes [16,24], sex [3,12,16,33], educational level [16], and physical activity [16] are significantly associated with diabetes related knowledge.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Having a father with middle and secondary school educational level increases 2.261 and 2.455 folds the level of knowledge about diabetes respectively. Sitaula et al [23] in Nepal found that a higher degree of parental education, in association with other factors, were signi cantly associated with good knowledge levels on both diabetes and hypertension.…”
Section: Discussionmentioning
confidence: 98%